Análisis crítico del examen de los documentos en las cartas de crédito - Gallegos Zúñiga, Jaime Ramiro (2015)
This article discusses the documents’ test that must be practiced during the issuance of letters of credit, so that subjects acting in international trade can meet the obligations involved by participating entities and challenge deficiencies in such benefits —if it’s the case—.